Penerapan Metode SMART dalam Penentuan Karyawan Terbaik pada Instansi XYZ - Syifa Wahyuni; Desi Pibriana (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
XYZ Agency is one of the Implementation Units under the auspices of the South Sumatra Regional Office. This agency has 70 employees divided into 5 divisions. The assessment of the best employees is useful for directing employee behavior and attitudes to produce good and quality performance. This agency has conducted an assessment of the best employees every month, carried out using observation and a pointing system so that it is still subjective and there is no weighting of criteria. The creation of a Decision Support System (DSS) for determining the best employees aims to improve accuracy and efficiency in calculating employee performance. This study uses the Simple Multi Attribute Rating Tachyon (SMART) calculation method and sets several criteria such as Attendance, Performance, Responsibility, and Attitude. In decision making, the SMART method is more commonly used because it can easily accommodate decision-making needs and make it the right choice in the context of this study.